Effect of hypohydration on gastric emptying and intestinal absorption during exercise - Ryan, A. J.; Lambert, G. P.; Shi, X.; Chang, R. T.; Summers, R. W.; Gisolfi, C. V. (Journal of Applied Physiology, 1998)
Dehydration and hyperthermia may impair gastric emptying (GE) during exercise; the effect of these alterations on intestinal water flux (WF) is unknown. Thus the purpose of this study was to determine the effect of hypohydration (approximately 2.7% body weight) on GE and WF of a water placebo (WP) during cycling exercise (85 min, 65% maximal oxygen uptake) in a cool environment (22 degrees C) and to also compare GE and WF of three carbohydrate-electrolyte solutions (CES) while the subjects were hypohydrated. GE and WF were determined simultaneously by a nasogastric tube placed in the gastric antrum and via a multilumen tube that spanned the duodenum and the first 25 cm of jejunum. Hypohydration was attained 12-16 h before experiments by low-intensity exercise in a hot (45 degrees C), humid (relative humidity 50%) environment. Seven healthy subjects (age 26.7 +/- 1.7 yr, maximal oxygen uptake 55.9 +/- 8.2 ml . kg-1 . min-1) ingested either WP or a 6% (330 mosmol), 8% (400 mosmol), or a 9% (590 mosmol) CES the morning following hypohydration. For comparison, subjects ingested WP after a euhydration protocol. Solutions ( approximately 2.0 liters total) were ingested as a large bolus (4.6 ml/kg body wt) 5 min before exercise and as small serial feedings (2.3 ml/kg body wt) every 10 min of exercise. Average GE rates were not different among conditions (P > 0.05). Mean (+/-SE) values for WF were also similar (P > 0.05) for the euhydration (15.3 +/- 1.7 ml . cm-1 . h-1) and hypohydration (18.3 +/- 2.6 ml . cm-1 . h-1) experiments. During exercise after hypohydration, water absorption was greater (P < 0.05) with ingestion of WP (18.3 +/- 2. 6) and the 6% CES (16.5 +/- 3.7), compared with the 8% CES (6.9 +/- 1.5) and the 9% CES (1.8 +/- 1.7). Mean values for final core temperature (38.6 +/- 0.1 degrees C), heart rate (152 +/- 1 beats/min), and change in plasma volume (-5.7 +/- 0.7%) were similar among experimental trials. We conclude that 1) hypohydration to approximately 3% body weight does not impair GE or fluid absorption during moderate exercise when ingesting WP, and 2) hyperosmolality (>400 mosmol) reduced WF in the proximal intestine.